Pengembangan Auto CAD dengan vB untuk Desain Pola Coran dan Cetakan Produk Pulley Standar Tipe Taper Lock - Muhammad Kusumawan Herliansyah (Forum Teknik, 2004)
dan  Adi NugrohoJl.  Grafika  No.  2,  Kampus  UGM,  Yogtakarta  55281AbstractThis paper  presents the  development  of  automatic casting  design  system for Taperlockpulley  type.  This  system  is  intended  to  assist  casting  designer  in  pattern design,  to  reduce  designtime,  and  to  minimize error  in  transfering  product  design  data into  pattern  design.The input  of this  system  is  data  base  of taper  lock  pulley's  catalogue  in  mdb format, whilethe  output  is  design of the  pattern  drawing  in  2D and  3D  solid. Moreover to  generate  patterndesign  is  around  59 second.Keywords:  casting,  pattern,  automat  ic.l.